A review of the genus Docleomorpha Hering (Lepidoptera, Zygaenidae, Chalcosiinae) with descriptions of four new species - Huang, Si-Yao; Horie, Kiyoshi; Espeland, Marianne (Zootaxa, 2025)
The taxonomy of the genus Docleomorpha Hering, 1922 is updated. Two new species are described from the Philippines: D. epsilon Huang & Horie sp. nov. and D. zeta Huang & Horie sp. nov. The genus is also recorded from Borneo, Malaysia for the first time with two new species described: viz. D. violae Huang & Horie sp. nov. and D. zhaoi Huang & Horie sp. nov. Adults and genitalia of the aforementioned taxa are illustrated.